An unusual case of anisocoria in a child with bleeding aneurysm of posterior communicating artery and idiopathic thrombocytopenic purpura (ITP) - Mahapatra, NC; Bandyopadhyay, A; Samanta, SK; Dolui, S; Fariduddin, K (Nepalese Journal of Ophthalmology, 2011)
Background: It can give rise to bleeding episodes in different parts of the body including the central nervous system with various systemic manifestations. Case: An eight-year old female child, diagnosed as a case of chronic ITP for last two years, developed intense headache and vomiting for a few days before admission. This was associated with right sided mid dilated pupil with brisk reaction to light. MRI-angiography showed a bleeding aneurysm of posterior communicating artery. The features of raised intra cranial tension subsided with conservative management but the anisocoria persisted. Conclusion: A bleeding aneurysm can manifest with anisocoria as a sign of partial third cranial nerve palsy. Key words: ITP, children, leaking aneurysm, anisocoria DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5276 Nepal J Ophthalmol 2011; 3(2): 191-192